Determinant Of Stakeholders Reliance On Indonesian Islamic Banking - Suharto, Sonia Maulina; Himawan, Hilmi Satria; Mubarok, Arif; Hakim, Sofyan; Amelia, Verra Rizki (BALANCE: JOURNAL OF ISLAMIC ACCOUNTING, 2024)
Islamic banking carries out business activities based on sharia principles. The economic growth of a country can be seen from the growth of financial institutions such as the banking sector. The influence of the banking sector in a country's economy is very large. The failure of a bank can have systemic consequences for a country's economy, whether conventional banking or sharia banking. This research aims to analyze and test the influence of sharia compliance reports towards the level of stakeholder trust on Indonesian Islamic banking. The indicators used in sharia compliance are profit sharing ratio, Islamic income ratio, and zakat performance ratio, while the indicators used in the level of stakeholder trust are third party funds This research approach uses quantitative methods with ex-post facto (cause-and-effect) research. The population in this research is Sharia Commercial Banks and Sharia Business Units registered with the Financial Services Authority in 2020-2022. Sample selection was carried out using a purposive sampling method, resulting in 13 Sharia Commercial Banks and Sharia Business Units for the 2020-2022 period. The data analysis method in this research is using Eviews 12. The results of this research show that partially the profit sharing ratio and Islamic income ratio have a positive and significant effect towards the level of stakeholder trust. The zakat performance ratio does not have a significant effect towards the level of stakeholder trust. Meanwhile, simultaneously sharia compliance has a positive and significant effect towards the level of stakeholder trust of 26.45%.